(untitled) (Tempo e Argumento, 2024)
On April 1, 1964, a coup d’état removed João Goulart from the presidency of the Republic. The objective was to depose the president, but not to impose an authoritarian regime. However, in the following eight days, the military and various social organizations, the press in particular, defended punishments for the so-called “communists”. The result was the Institutional Act of April 9, paving the way for the establishment of dictatorship in the country. Using the press as a privileged source and using a micro-analytical approach, the research points to the collusion of the press, political institutions and various social organizations with the military authoritarian.